Impact of external forces on the quality of digital elevation model derived from drone technology - Isola, Ajibola Ismaila; Mansor, Shattri; Shafri, Helmi; Pradhan, Biswajeet; Mansor, Yaakob (Association for Geoinformation Technology, 2019)
Platform instability is one of notable causes of error in Digital Elevation Model (DEM) derived from a low altitude aerial survey. This paper explores the influence of atmospheric pressure (AP) on a drone derived DEM. To achieve the research objective, an experiment was carried out using a fixed-wing drone that was flown over a Golf course at the Universiti Putra Malaysia. The drone with an on-board camera captured photos of the study area at a predefined regular time interval. Prior to aerial survey, some ground control points (GCPs) were placed in the study area for image processing and quality assessment. Then flew the drone to capture photos of the study area at seven different altitudes (100m, 150m, 200m, 250m, 350m, 400m, and 500m). An image-matching algorithm was used to process the photos. In the end, seven DEMs were exported in tiff file format. More analysis was carried out with a proposed model to reveal the impact of AP on the resulting DEMs. The impact of AP on DEMs acquired at altitudes stated above are 0.072m, 0.05m, 0.014m, 0.01m, 0.004m, 0.003m, and 0.002m in that order. The results were validated using height of the GCPs and their matching points on the DEMs. The validated test produced RMSE of 0.03m, 0.05m, 0.07m, 0.1m, 0.13m, 0.14m, and 0.16m in that order of altitudes earlier mentioned above. The results reveal that the AP has a small effect on the DEMs. Hence, the impact of AP can be ignored amid of all external forces that can influence the quality of DEM derived by drone system.